Peningkatan Kualitas Pendidikan Oleh Mahasiswa KKN di Desa Domas Kecamatan Trowulan Kabupaten Mojokerto - Riska Ayu Rahmaida; Alifatur Mustofa; Sjarief Hidajat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Education is a crucial foundation for building quality human resources and community welfare. The Thematic Community Service Program (KKN) conducted by students of UPN